Microbiological contamination sources of freshly cultivated vegetables. Issue 4 (13th July 2015) - Alam, Md. Sajjad; Feroz, Farahnaaz; Rahman, Hasibur; Das, Kamal Kanta; Noor, Rashed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the paper is to emphasize on contamination sources of freshly cultivated vegetables commonly consumed by the Bangladeshi people. Several local studies have been conducted to detect the microbial contamination within fresh vegetables, plantation lands and the irrigation waters separately; however, the correlation of microbial contamination between the fresh produces and the surrounding environment has not been clarified. Design/methodology/approach – Bottle gourd (Lagenaria siceraria), pumpkin (Cucurbita pepo), radish (Raphanussativus) and eggplant (Solanummelongena); their plantations soils and the fertilizers applied across the agricultural lands; and, finally, the irrigation waters used were analyzed from nine districts of Bangladesh using conventional microbiological and biochemical methods. Findings – Almost all vegetable samples studied were found to be immensely contaminated with bacteria and fungi. Among the pathogens, Klebsiella spp., Staphylococcus spp. and Pseudomonas spp. were found to be dominant. Besides, massive microbial growth was also observed in the plantation soils and fertilizers, including Klebsiella spp., Pseudomonas spp., Bacillus spp., Listeria spp., Escherichia coli and Vibrio spp. Existence of the fecal coliforms, E. coli, Klebsiella spp., Salmonella spp. and Listeria spp., was noticed in the irrigation waters. Research limitations/implications – Although the present study revealed the combined results connecting the vegetable contamination aspect with the knowledge on microbiology ultimately in the food chain, implementation of molecular studies detecting the virulence genes both in the fresh produces and the plantation soils, fertilizers and the irrigation waters would further clarify the microbial dissemination mechanism. Practical implications – Earlier studies demonstrated the ability of water bodies to disseminate numerous microorganisms into the plantation soils, and to some extent unraveled the ability of organic fertilizers to propagate pathogenic bacteria into the vegetation objects. These microorganisms may pose as a threat to vegetables, particularly by limiting crop production as well as the shelf life of the fresh produces. Social implications – The scenario of microbial divergence not only in the vegetables but also within the surroundings is gradually being heightened in Bangladesh principally due to the malpractice of sanitation, dumping the agricultural lands with feces, improperly controlled septic systems, waste water runoff across the agricultural lands, etc. Therefore, the preliminary and replicable experimental approach described in the current study would be feasible for all other developing countries to maintain the public health safety. Originality/value – Growth and proliferation of microorganisms both in the vegetable samples and the environmental samples nearly to a similar extent indeed projected for the first time in Bangladesh, the agricultural perspective of the contamination sources of vegetables. Such knowledge would aid in the existing knowledge on the hygienic processing during crop production and harvesting for the sake of better consumer safety management.